Numerical simulations of cathode directed streamer propagation in electronegative gases - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2018)
The numerical simulations are carried out for the cathode directed streamer propagation at the quasi-stationary
stage, far from electrodes, and at the stage of going out to cathode, in the gases with the different combinations of
three-body and dissociative attachment. The typical features of the process in presence of intensive attachment are
revealed. Виконано числове моделювання поширення катодоспрямованого стримера на квазістаціонарній стадії,
далеко від електродів, та на стадії виходу на катод у газах з різним поєднанням трьохтільного та дисоціативного приставання. Виявлено типові риси процесу за наявності інтенсивного приставання. Выполнено численное моделирование распространения катодонаправленного стримера на квазистационарной стадии, вдали от электродов и на стадии выхода на катод в газах с разным сочетанием трехтельного
и диссоциативного прилипания. Выявлены типичные черты процесса при наличии интенсивного прилипания.